67.6k views
4 votes
Consider the combined function

Consider the combined function-example-1
User Karlcow
by
6.3k points

2 Answers

6 votes
A is the right answer
User Sealroto
by
5.5k points
3 votes

Given:

f(x)=4x-3

f(x) +g(x) =9x +4

To find:g(x)

Solution:

f(x) + g(x) =9x +4

Replacing f(x) with its value.

4x -3 +g(x) = 9x +4

=> g(x) = 9x+ 4 -(4x-3)

=> g(x) = 9x+4 -4x +3

=> g(x) = 5x +7

Hence;

Option A g(x)=5x+7 is the answer.

Hope it helps...

Regards;

Leukonov/Olegion.

User Stamatis
by
5.6k points